A Sociological Analysis of Child Abuse and Psychological Trauma in Colleen Hoover’s Hopeless - Ramadani, Nadya; Purwarno, Purwarno (Universitas Islam Sumatera Utara, 2026)
This study examines the representation of child abuse in Hopeless by Colleen Hoover, focusing on the experiences of the protagonist, Sky Davis, also known as Hope. It aims to identify the forms of child abuse depicted in the novel and to analyze their psychological effects on the main character. In this research, child abuse is defined as any form of maltreatment inflicted upon a child, including physical and emotional abuse, educational and medical neglect, and sexual violence. Using a qualitative research design, the data were collected from relevant quotations and significant narrative events in the novel. The analysis is based on the theoretical frameworks of child abuse proposed by Siswanto (2007) and Shackelford (2021). The findings reveal that Sky is a victim of sexual abuse committed by her biological father during her childhood. This traumatic experience leaves profound and lasting psychological scars, significantly influencing her emotional and behavioral development. As a result, Sky exhibits symptoms of phobia, post-traumatic stress disorder (PTSD), and aggressive behavioral tendencies. Ultimately, the novel vividly portrays the devastating long-term impact of child abuse on an individual's mental health, personal identity, and capacity to form healthy interpersonal relationships.